Potential Demand for Alternative Fuel Vehicles - John K. Dagsvik; Dag G. Wetterwald; Rolf Aaberge (Statistics Norway, Research Department, 1996)
This paper analyzes the potential household demand for alternative fuel vehicles in Norway, by applying data from a stated preference survey. The alternative fuel vehicles we consider are liquid propane gas and electric powered vehicles in addition to a dual-fuel vehicle. In this survey each respondent, in a randomly selected sample, was exposed to 15 experiments. In each experiment the respondent is asked to rank three hypothetical vehicles characterized by specified attributes, according to the respondent's preferences. Several versions of a random utility model are formulated and estimated. They include the ordered logit model and a model with preferences that are correlated across experiments. The model is applied to predict changes in demand resulting from price changes, and to assess the willingness to pay for alternative fuel vechicles.
Keywords: C51; C93; D12; 330; Stated preference; random utility; alternative fuel vehicles; ordered logit model; serially dependent preferences.